Effect of Damping on Simple Vibrational Systems - Eyad Maaly; Jafar Robu; Huthaifa Nahawi; Rafat Ghannam (My University, 2011)
Abstract             In this project we will discuss four type of damping by mention the definition for each one and talking in generally about their characteristics and the way to measurement for each one and study the effect for each one on the vibration system we mean free and force vibration system. In chapter one we will definition the damping and mention the type of damping that we will study in our project and in chapter two we will talk about the viscous damping and some characteristics for it and how it effect on free and vibration system and In chapter three we will also talk about the second type of damping (Coulomb Damping) and how it effect on the free and force vibration system and in chapter four we will talk about the Hysteresis Damping by mention three model for it and discus the way that it effect on free and vibration system and in chapter five we will talk in generally about magnetic damping  and we will in last chapter discuss application of damping by designing a simple advice (measurement device) to calculate the ( ) damping ratio for   viscous damping and how we can used it to know the type of the fluid.